2016
DOI: 10.1039/c6ra20680h
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-homogenized matrix solid-phase dispersion coupled with gas chromatography – electron-capture negative-ion mass spectrometry to determine halogenated phenolic compounds in seafood

Abstract: This work represents the development of vortex-homogenized matrix solid-phase dispersion (VH-MSPD) as an effective and simple method to rapidly extract halogenated phenolic compounds in marketed seafood samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The linearity was also confirmed by a Mandel's fitting test. 25 As shown in Table 1 , all of the calculated F -values were lower than the tabulated limit ( F tab = 10.13) at a 95% confidence level, thus confirming that the linear regression fits the experimental data better than quadratic regression.…”
Section: Resultssupporting
confidence: 60%
“…The linearity was also confirmed by a Mandel's fitting test. 25 As shown in Table 1 , all of the calculated F -values were lower than the tabulated limit ( F tab = 10.13) at a 95% confidence level, thus confirming that the linear regression fits the experimental data better than quadratic regression.…”
Section: Resultssupporting
confidence: 60%
“…The results we obtained suggest that the sample preparation before the DLLME procedure and the miniaturization of what was proposed by Wang et al (2013) led to satisfactory results for TBBPA quantification even in complex matrices. For solid environmental matrices, most of the methods rely on SPE, with conventional (C 18 cartridges; Deceuninck et al 2014; Regueiro and Wenzl 2015; Chi et al 2017; Li et al 2017) or alternative sorbent materials (Chen et al 2016; Hu et al 2019), requiring a large volume of solvents for cartridge activation and analyte elution.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the presence of TBBPA in complex matrix samples, extraction and clean‐up methods are still based on nonminiaturized techniques. Analytical methods to determine the presence of tetrachlorobisphenol A, pentabromophenol, bisphenol A, TBBPA, hexabromocyclododecane, polybrominated diphenyl ether, and bromophenols in complex solid and aqueous samples based on the use of a larger volume of organic solvent, SPE cartridges, time‐consuming steps throughout the procedure, and a complex apparatus compared with DLLME procedures have been extensively reported (Deceuninck et al 2014; Chen et al 2016; Zhang et al 2016; Chi et al 2017; Li et al 2017). For complex environmental samples, the DLLME technique may be combined with other extraction and/or clean‐up procedures depending on the nature of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Asshown in Table , linearities (coefficient of determination r 2 >0.9992) were found in the five‐level calibration curve ranging from 50 to 5000 ng/L. The calculated linearity was further confirmed using Mandel's fitting test . The calculated F ‐values, which ranged from −2.022 to 4.01 and were lower than the tabulated limit ( F tab = 10.13) at the 95% confidence level (Table ), demonstrated that linear regression (instead of quadratic) fit the experimental data the best.…”
Section: Resultsmentioning
confidence: 99%